Analysis of the tripartite interactions between two bacterial symbionts, a novel Solitalea-like bacterium (Bacteroidota) and Cardinium, and the stored product mite Tyrophagus putrescentiae based on gene expression data - Hubert, Jan; Xiong, Qing; Glowska-Patyniak, Eliza; Furtak, Elizabeth V; Klimov, Pavel B (Microbiology spectrum, 2025)
UNLABELLED: The intracellular parasite Cardinium influences the bacterial microbiome composition of arthropod hosts; however, the mechanisms involved remain poorly understood. We sought to evaluate the interactions between Cardinium (cTPut) and SOL in Tyrophagus putrescentiae cultures based on relative abundance and gene expression data. First, we assembled the genome of Candidatus Krakonobacterium acarorum (formerly the Soliltalea-like symbiont SOL), a novel lineage of the Bacteroidota symbiont of mites. The assemblage SOL genome (1.2 Mb) contained complete pathways for the biosynthesis of lipoic acids, pantothenate, and menaquinone from futalosine. SOL is considered a facultative inhabitant (with prevalences ranging from 36% to 80% among individuals) of the gut (from 102 to 104 copies/mite) that is not detected in eggs, suggesting an extracellular location in the gut of mites. Second, gene expression was analyzed in SOL-inhabited cultures, including two cultures with cTPut and two cultures without cTPut. Correlation-based evidence for competition between cTPut and SOL was found mainly in the expression of transporter proteins. The presence of cTPut decreased interactions between SOL and the mite host; however, SOL is under greater control by mites in the presence of cTPut than in the absence of cTPut. Mite KEGG gene expression levels in the peroxisome, autophagy, sphingolipid, apoptosis, PI3K-Akt, and lysozyme pathways were more strongly correlated with SOL gene expression in cultures without cTPut than in those with cTPut. In contrast, mite KEGG gene expression levels in the proteasome, NF-κB, TNF, calcium, and Rap1 signaling pathways were more strongly correlated with SOL in the presence of cTPut. The explanation for these results is that cTPut mostly interacts with the mite host, resulting in changes in the host's immunity-related/regulatory pathways, indirectly affecting the symbiont SOL. IMPORTANCE: Here, we describe the novel Bacteroidetes symbiont (SOL) of mites. The analysis of gene expression in meta-transcriptomic samples from cultures with and without the intracellular parasite Cardinium revealed the effect of Cardinium on SOL as a model facultative symbiont of mites. Our findings suggest that there is competition between these two symbionts for nutrients. In addition, Cardinium can influence other bacterial symbionts via mite host immunity-related and regulatory pathways. Tyrophagus putrescentiae is a cosmopolitan pest mite that contaminates the home environment, including stored food and feed, with allergens. The interactions between intracellular bacteria and other members of the microbiome influence host physiology and indirectly affect allergen production.
Keywords: roztoči; genom bakteriální; Phylogeny; symbionts; gene expression; Mites; Bacteroidota; interaction; Acaridae; mite; symbióza; zvířata; Bacteroidetes; Symbiosis; fylogeneze; stanovení celkové genové exprese; Animals; Genome, Bacterial; Gene Expression Profiling; Cardinium